Social Context of Civil Process for Sustainable Development - Kharitonashvili, Nino (European Scientific Journal, ESJ, 2024)
This paper focuses on the existing mechanisms for the participation of vulnerable persons, including persons with disabilities and children, in civil disputes. As modern democratic society develops the concept of a social state, ensuring equal conditions for the participation of vulnerable persons in civil turnover is essential. Hence, the aim of the study is to identify existing legislative gaps and challenges that prevent the participation of vulnerable persons in civil disputes. Humanity has agreed on a sustainable development plan, in which social sustainability is set as one of the main goals. However, modern civil procedure law is mainly based on the codification of the 19th century, which in turn originates from Roman law. Since then, public relations have changed and modern technologies are constantly developing. The concept of a digital judge, smart contracts, and a blockchain system has already emerged. Therefore, the regulations of civil proceeding do not respond to modern challenges, and it is necessary to update civil procedure legislation in order to provide an equal platform for the participation of vulnerable persons in civil disputes. The purpose of the article is to review the rules of civil procedure law in terms of a social context based on the international approaches, practices, and research. Through a mixed-quantitative, qualitative, and general research methods, as well as comparative analysis, specific recommendations are introduced that will bring civil dispute resolution closer to sustainable development plans and ensure the equal participation of vulnerable persons in civil dispute.